Paradoxical effects of chemotherapy on tumor relapse and metastasis promotion. (February 2020) - D'Alterio, Crescenzo; Scala, Stefania; Sozzi, Gabriella; Roz, Luca; Bertolini, Giulia
Abstract: Several lines of compelling pre-clinical evidence identify chemotherapy as a potentially double-edged sword: therapeutic efficacy on the primary tumor may in fact be counterbalanced by the induction of tumor/host reactive responses supportive for survival and dissemination of cancer cell subpopulations. This paradoxical effect of chemotherapy can affect different districts such as the primary tumor, the circulation and distant organs by simultaneously shaping properties and composition of tumor and stromal cells. At the primary tumor site, chemotherapy has been reported to promote selection of chemoresistant and disseminating tumor cells endowed with properties of cancer stem cells (CSCs) through activation of autocrine and paracrine self-renewing/survival pathways promoted jointly by therapy-selected tumor and stromal cells. Resistant CSCs represent seeds for tumor relapse and increased infiltration by immune cells, together with enhanced vascular permeability induced by chemotherapy, facilitates tumor cells intravasation, the first step of the metastatic cascade. As a consequence of primary tumor/metastasis re-shaping induced by chemotherapy, circulating tumor cells (CTCs) detected during therapy can display a shift towards a more mesenchymal and stem-like phenotype, conductive to increased ability to survive in the circulation and seed distant organs. At the metastatic site, host responses to therapy activate inflammatory pathways that ultimately facilitate tumor cells extravasation and metastatic colonization. Finally, cooperation of immune cells and endothelial cells at perivascular niches favors the extravasation of tumor cells endowed with high potential for metastasis initiation and protects them from chemotherapy. This review highlights the paradoxical pro-metastatic effects of chemotherapy linking reactive responses to treatment to tumor relapse and metastasis formation through primary tumor remodeling and generation of a favorable pro-metastatic niche.